Effects of caffeic acid on the growth performance, growth genes, digestive enzyme activity, and serum immune parameters of beluga (Huso huso). Issue 7 (2nd June 2022) - Ahmadifar, Ehsan; Mohammadzadeh, Sedigheh; Kalhor, Naser; Salehi, Farzin; Eslami, Mahboubeh; Zaretabar, Amine; Moghadam, Mohsen S.; Hoseinifar, Seyed H.; Van Doan, Hien
Abstract: Caffeic acid is a phenolic metabolite known for its beneficial pharmaceutical effects and is suggested as a functional additive for aquaculture. In this study, the effects of caffeic acid on the growth performance, growth genes, digestive enzyme activity, and serum immune parameters of beluga ( Huso huso ) were investigated. For this purpose, 120 beluga juveniles (367.75 ± 21.32 g) were divided into 12 tanks and fed with caffeic acid at rates of 0 (T0, control), 1 (T1), 5 (T2), and 10 (T3) g/kg for 56 days. The final weight and weight gain of beluga were significantly higher in fish fed 5 (T2) and 10 (T3) g caffeic acid/kg than in the control group and 1 (T1) g caffeic acid/kg. The specific growth rate was significantly higher in beluga fed 10 g caffeic acid/kg than 0 and 1 g/kg. Compared with the control group, the amylase, lipase, and pepsin activities were significantly higher in T2 and T3. The relative expression of growth hormone and insulin‐like growth factor significantly increased in T3 compared with the control group. The expression of lipoprotein lipase and nuclear factor interleukin 3 of beluga fed 5 and 10 g caffeic acid/kg was higher than the control group. The lysozyme activity, total immunoglobulin, and total protein in the serum of beluga significantly increased in fish fed with caffeic acid at different rates compared with the control group. Based on the finding, the results suggested that the inclusion of caffeic acid (5–10 g/kg) in the diets of beluga is recommended to enhance the growth performance, some digestive enzyme activity, and serum immune parameters. Abstract : Caffeic acid had a positive effect on growth performance. Dietary caffeic acid supplementation enhanced digestive enzymes activity and growth relative gene expression. Dietary caffeic acid increased lysozyme activity, total immunoglobulin, and total protein compared with the reference group. Caffeic acid at the rate of 5–10 g/kg was more efficient in comparison with the reference group. Highlights: Caffeic acid had positive effect on growth performance. Dietary caffeic acid supplementation enhanced digestive enzymes activity and growth relative gene expression. Dietary caffeic acid increased lysozyme activity, total immunoglobulin, and total protein compared with the reference group. Caffeic acid at the rate of 5–10 g/kg was more efficient in comparison with the reference group.